Inducción de callos embriogénicos en tallos de Persea americana Mill. “palto” cultivar fuerte utilizando diferentes concentraciones de 2,4-Diclorofenoxiacético y 6-Bencil Amino Purina - Hostia Rodriguez, Karen Jannet (2017)
Since 2011, region La Libertad is the most important avocado producer of the country, which, combined with a high production and exports of their fruits, makes this species in a high interest agro-economic resource for the region development. In vitro culture is a fundamental step in the production and regeneration of genetically modified plants, or transgenic, through biotechnology techniques, so that the clonal propagation through embryogenesis has become an essential method for the improvement of most economically important plants, reducing the time required for the propagation of plants. Therefore, the objective of the work was to induce embryogenic callus on steams of Persea Americana Mill. "palto" fuerte culture, using different concentrations of 2,4-Dichlorophenoxyacetic (0 and 0.1mg/L) y 6-Benzyl Amino Purine (0, 1, 5 and 10mg/L). Ten 120-day-old fuerte culture plants and 150 explants were used. The evaluations per treatment were every 15 days. It was found that the highest percentage of induction of embryogenic callus was 94% at 0 mg/L of 2,4-Dichlorophenoxyacetic and 5 mg/L of 6-Benzyl Amino Purine, moreover the callus obtained in this treatment presented in its morphology green coloration with sinuous concave shape and a growth rate of 0.20 %. Key words: